Microbial hosts for production of D-arabitol: Current state-of-art and future prospects. (February 2022) - Ravikumar, Yuvaraj; Razack, Sirajunnisa Abdul; Ponpandian, Lakshmi Narayanan; Zhang, Guoyan; Yun, Junhua; Huang, Jiaqi; Lee, Donghun; Li, Xiaolan; Dou, Yuan; Qi, Xianghui
Abstract: Background: D -arabitol, being a xylitol enantiomer with a caloric value (0.2 kcal/g) much lower than sucrose occurs typically in yeasts and higher fungi when these organisms are under environmentally stressed conditions. Credited with such beneficial properties, the United States Department of Energy in 2004 has subsumed it as one among the twelve useful building-block chemicals for biorefinery. Current industrial production employs chemical synthesis which includes two-step hydrogenation process using arabinoic acid and lactones as a starting material. Scope and approach: Due to its limited availability in natural sources, maneuvering strategies for D -arabitol production via biological process might cater to a scalable yield in the future. Herein, a detailed summary on strain improvement, where the scope of metabolic and genetic engineering methods to engender yeasts strains for improved arabitol production is highlighted. Further, the importance of understanding the metabolic pathway that regulates D -arabitol synthesis and its significant influence in optimizing the fermentation process is also briefly summarized. Key findings and conclusions: Producing D -arabitol by yeast chiefly involves fermenting glucose and glycerol . Elucidating the D -arabitol biosynthesis pathways and regulatory mechanism has elevated the researcher's interest in engineering the host strain by mutagenesis, genome shuffling, metabolic engineering, and regulators for increasing D -arabitol titers. Nevertheless, rapid progress in the past half-decade culminating in the synthesis of D -arabitol from cheap renewable sources and byproducts that arise during biodiesel production are reviewed. In the future, along with the approaches mentioned above, works focusing more on building prokaryotic hosts ( E. coli, B. subtilis, etc.) via synthetic biology will drive the D -arabitol production closer to the industries that would benefit humanity. Highlights: 1. D -arabitol is one among the top-twelve useful building blocks for biorefinery. Yeasts serve as an important microbial host for D -arabitol biosynthesis. Genome and metabolic engineering help the yeast to enhance the D -arabitol yields. Feasibility of xylose, arabinose and glycerol for D -arabitol synthesis are highlighted. Fermentation and pentose phosphate pathway regulation influence D -arabitol yields.